Conceptual Design Of Biodiversity Data Model (BiDaM) Using Object Relational And Event Based Approach - Kamruzzaman, A. Z. M. (2005)

(untitled)
The complexity of natural history collection information and similar information within the scope of biodiversity informatics poses significant challenges for effective management of plant biodiversity data with database system. Plant biodiversity is the variety of different types of plants species that growth in various landscape. Various data models, query languages and techniques have been proposed by many researchers. Traditional database systems which are widely used for commercial applications but those models fail to meet biological application (biodiversity data). This paper discusses about the conceptual design, how spatio-temporal data can make enhancement plant biodiversity data model design for long term stewardship of biodiversity information. Plenty of data model has been developed (such as BODHI), which is only support spatial data. In addition to this, most of the data models are relational model. Geographical data have an object and location, attribute and time. Integration between plant Biodiversity data and geographical data with event-based approach can make an enhancement for the plant biodiversity data analysis and data manipulation. Main purpose of this paper is to design a conceptual plant biodiversity data model which is combination of BODHI data model and event-based techniques by using object relational approach to support temporal data.